Endocrine morbidity and growth impairment in β-thalassemia intermedia: Insights from 25 years of multinational studies - Soliman, Ashraf T; De Sanctis, Vincenzo; Ahmed, Shayma; Alyafei , Fawzia; Alaaraj, Nada; Hamed, Noor; Elsayed , Shaymaa; Fawzy , Dina; Soliman, Nada (Acta Biomedica Atenei Parmensis, 2025)
Background: β-thalassemia intermedia (β-TI) represents a heterogeneous spectrum of severity. Although patients typically require fewer transfusions than those with β-thalassemia major, they remain at risk of iron overload from increased intestinal absorption and occasional transfusions. This iron burden, combined with chronic anemia, contributes to growth impairment and endocrine complications. Objectives: This review summarizes evidence on growth and endocrine outcomes in β-TI, describing prevalence patterns across regions, differences related to transfusion practices, and the quality of available research. Methods: PubMed, Scopus, and Google Scholar were searched through March 2025. Eligible studies included ≥10 patients with clinically or genetically confirmed β-TI and reported prevalence of short stature, growth hormone deficiency (GHD), hypogonadism, delayed puberty, hypothyroidism, hypoparathyroidism, diabetes mellitus (DM), or impaired glucose tolerance (IGT). Data on study design, sample characteristics, transfusion history, and iron indices were extracted. Study quality was assessed with modified MINORS and Cochrane criteria. Results: Eighteen studies from the Middle East, Asia, the Mediterranean, and North America were reviewed. Short stature affected 21–46% of patients, with higher rates in non-transfused cohorts. GHD was reported in 26–31%. Hypogonadism and delayed puberty occurred in 5–25%, particularly in intermittently transfused patients with greater iron load. Hypothyroidism varied from absent in pediatric groups to >20% in older cohorts, with subclinical cases more common. Hypoparathyroidism was rare (<2–4.4%). Abnormal glucose metabolism was observed in 2–25%, closely linked to hepatic iron burden. Large multicenter studies generally reported lower prevalence than small single-center series. Conclusions: Growth failure and endocrine abnormalities are common in β-TI, regardless of transfusion dependence. Variations reflect geography, iron overload, and healthcare resources. Standardized endocrine surveillance and multicenter collaborations are essential to improve early detection and management.